KLASIFIKASI KARAKTER REBABAN GAYA SURAKARTA - Bambang Sosodoro (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2014)
In essence, this study examines a concept contained in rebaban Surakarta style. Ie terms that relate to the character or flavor rebaban, such as: prasaja, whole, Alus, anteb, mbranyak, sigrak, tregel, prenes, rongeh, cakrak, and Berag. In Javanese musical life until today, the phenomenon of the terms are still often encountered. Statements about the character rebaban, always pointing at someone (pengrebab). Wahyopangrawit example, is a fairly popular figure pengrebab and phenomenal musical community with the whole character and Alus. Likewise pengrebab-pengrebab others, certainly has character rebaban different. Among musicians, generally found rebaban character is a representation of a personal character, the nature of the person, or a reflection of their daily behavior. On the other hand, the character rebaban also part of working on. Is how the tenants (pengrebab) seeks to match the character of the musical piece, which basically has been built by the games ricikan, especially ricikan working on ngajeng. This study seeks to formulate characters rebaban based on the views by the musicians. Labih Further, these characters are classified or grouped based on its characteristics. Broadly speaking, the character can rebaban dipilahkan into two large families, which is shed and mbranyak. Both of these families have a sub-sub-characters, namely: prasaja and Alus is entered on the whole character of the area, while the character mbranyak include characters: prenes, tregel, cakrak, rongeh, and Berag. Among these characters, there are some that are highly aggregated, but also there are a number of characters that can be said to be similar, identical, or color. Rebaban medium of expression is one of the many mediums in Javanese gamelan. Rebaban also an expression of the artist’s soul, through the game hands and fingers.Keywords: classification, musichal character, rebaban